The Design of Social Pensions in Local Governments of Ibero-America - Rosas Arellano, Jarumy (Revista del CLAD Reforma y Democracia, 2018)
Social pensions to old age have become a key figure in social protection schemes in the world. Its main objective is to help to the prevention of the vulnerability in which older adults can commonly incur due to the lack or the significant reduction of their economic income. Usually, social protection and, therefore, social pensions, are designed and implemented by the central government. However, local governments in Ibero-America have shown interest for this schemes in the last few years. This paper aims to perform an exploratory analysis of the design of non-contributory or social pensions implemented by local governments in Colombia, Spain and Mexico, to identify their similarities and differences and recognize their contributions to the social security strategy of these contries. A documentary review was carried out to identify the existence of local social pension schemes in the second-order governments of 28 Ibero-American countries. 21 social pension programs were identified in this region. Basing on criteria of selection and availability of information, three case studies were selected: “Subsidio Distrital para el Adulto Mayor” in Barranquilla, Colombia; “Prestación complementaria a pensión no contributiva” in Catalonia, Spain; and “Atención a los ___________________________ adultos mayores” in Jalisco, Mexico. The results highlight that the selected cases are embedded and contribute to the social protection strategy of their respective nations. It was observed that the studied cases are of recent creation and appear in local governments as social programs. The need to evaluate local social pension programs was also observed with the intention of recognizing their feasibility, impact and if they respond to the context of older adults in their territories.